Further Thoughts on Dialectical Inquiry: A Rejoinder to Mitroff and Mason - Cosier, Richard A. (Academy of Management Review, 1981)
Mitroff and Mason suggest that the policy and planning field is largely metaphysical and beyond the scope of traditional scientific experimentation. From this premise, they argue that the dialectical approach was not properly operationalized in controlled experiments. I maintain that controlled experimentation is needed in policy and planning and that failure to accept unfavorable evidence regarding dialectical inquiry may reflect a general desire to dismiss experimental evidence about planning variables.